THE ROLE OF E-LEARNING AS A RESPONSE TO CRISES IN REDUCING THE SPREAD OF THE CORONAVIRUS A STUDY OF THE DECISIONS OF HIGHER EDUCATION AND SCIENTIFIC RESEARCH IN THE HASHEMITE KINGDOM OF JORDAN - ZAID ALMAHIRAH, MOHAMMAD SALAMEH (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the role of e-learning in limiting the spread of the Coronavirus through the decisions of the Ministry Higher Education in the Hashemite Kingdom of Jordan. The study consisted of 10 university presidents in Jordan. The descriptive analytical approach was used in the study. The arthematic means of e-learning came with a high degree of evaluation from the perspective of university presidents in the Hashemite Kingdom of Jordan, and this indicates the effectiveness of those methods in limiting the spread of the Coronavirus among students. The application of these methods contributed to alleviating mixing among students, and this in turn helps in reducing the spread of the virus. The results also showed that the preferred scenario among university presidents for the fundamental transformation that is related to the spread of the Coronavirus in terms of controlling and limiting it, is the application of the means and mechanisms of e-learning and the decisions and generalizations of the Ministry of Higher Education and Scientific Research in Jordan are an important stage in the recovery of Jordan and limiting the virus spread. The reason for the confirmation of university presidents is linked to the positive results in the application of e-learning to reduce this phenomenon.